IMPROVING ACCOUNTING OF LONG-TERM BIOLOGICAL ASSETS IN AGRICULTURE - Yusupova Mahfuza Bakhtiyar kizi (Scholar Express Journals, 2024)
This article covers the issues of accounting for long-term biological assets in agriculture. Definitions and approaches of the normative legal documents, foreign and domestic economists to the concept of biological assets have been researched. Proposals and recommendations have been developed to improve the accounting of long-term biological assets.
Keywords: agriculture; long-term biological assets; international standards of financial reporting